PERAN ALIRAN LINGUISTIK MODERN DALAM PENGEMBANGAN KURIKULUM BAHASA ARAB - Nurhalim; Nur Fatimatuzzahroh; Robi Irawan; Fachrul Ghazi (Al Ibrah: Journal of Arabic Language Education, 2026)
This study aims to analyze the role of modern linguistic schools in the development of the Arabic language curriculum and their relevance to contemporary Arabic language learning. The background of this research is based on the dominance of traditional approaches in Arabic language learning that focus mainly on grammar mastery and memorization, which are considered insufficient to meet communication needs and 21st-century competencies. This research employed a qualitative approach using library research methods. The data were collected through documentation of various scientific sources, including books, journal articles, and previous studies related to modern linguistics and Arabic language curriculum development. The data analysis technique used content analysis through the stages of data reduction, classification, interpretation, and conclusion drawing. The findings reveal that modern linguistic schools such as structuralism, behaviorism, generativism, sociolinguistics, and communicative linguistics significantly contribute to the development of the Arabic language curriculum in terms of learning objectives, material organization, teaching methods, and evaluation systems. The study also found that the integration of modern linguistics can transform the Arabic language curriculum into a more communicative, contextual, integrative, and adaptive system toward digital technological developments. Therefore, the development of the Arabic language curriculum in the contemporary era requires a multidisciplinary approach integrating modern linguistic theories and the demands of 21st-century learning. Abstrak Penelitian ini bertujuan untuk menganalisis peran aliran linguistik modern dalam pengembangan kurikulum bahasa Arab serta relevansinya terhadap pembelajaran bahasa Arab kontemporer. Latar belakang penelitian ini didasarkan pada masih dominannya pendekatan tradisional dalam pembelajaran bahasa Arab yang berorientasi pada penguasaan tata bahasa dan hafalan sehingga kurang mampu menjawab kebutuhan komunikasi dan kompetensi abad ke-21. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian kepustakaan (library research). Data penelitian diperoleh melalui dokumentasi berbagai sumber ilmiah berupa buku, artikel jurnal, dan hasil penelitian yang relevan dengan linguistik modern dan kurikulum bahasa Arab. Teknik analisis data menggunakan analisis isi (content analysis) melalui tahapan reduksi data, klasifikasi, interpretasi, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa aliran linguistik modern seperti strukturalisme, behaviorisme, generativisme, sosiolinguistik, dan linguistik komunikatif memiliki kontribusi signifikan terhadap pengembangan kurikulum bahasa Arab, baik dalam aspek tujuan pembelajaran, penyusunan materi, metode pembelajaran, maupun sistem evaluasi. Penelitian ini juga menemukan bahwa integrasi linguistik modern mampu mengarahkan kurikulum bahasa Arab menjadi lebih komunikatif, kontekstual, integratif, dan adaptif terhadap perkembangan teknologi digital. Dengan demikian, pengembangan kurikulum bahasa Arab di era kontemporer memerlukan pendekatan multidisipliner yang mengintegrasikan teori linguistik modern dan kebutuhan pembelajaran abad ke-21.